Teologi Digital Sebagai Konsep Dalam Pemberian Persembahan Via QRIS Memasuki Era Digital - Goni, Ebenhaezer Yoshua; Sumakul, Henny William Booth; Lumi, Altje (Jurnal Teologi Pambelum, 2025)
This article analyzes the relevance of digital theology as an approach to offering through the QRIS system in the digital era for the congregation of GMIM Kuranga Talete Dua. Digital theology views technology not just as a tool, but as a new space that can be used to actualize faith participation in a contextual and contemporary way. In this context, the use of QRIS as a medium for offerings is seen as a form of faith actualization for the congregation in the ever-evolving digital world. Offering through QRIS is not only efficient, but also reflects the church's openness to change and its efforts to reach the digital generation without being influenced by the negative impacts of technology. This analysis finds that the integration of theological understanding and the use of technology can strengthen the spirituality of the congregation while maintaining the sacred values of worship. Digital theology, therefore, serves as a relevant foundation for shaping an active and contributive lifestyle for the congregation amidst the digital reality.